Konsep Keselamatan dalam Teologi Armenian - Artariah Artariah; Ncihur Fronika Solin; Agustinus Gulo; Juita Selfia Manullang; Adi Suhenra Sigiro (Jurnal Silih Asuh : Teologi dan Misi, 2025)
This paper theologically examines the concept of salvation in Arminian theology, a system of thought developed by Jacobus Arminius in response to the doctrines of Calvinism, especially regarding predestination and saving grace. Through a literature study, this research explores the main tenets of Arminianism such as freedom of the will, conditional election, universal redemption, the resistibility of grace, and the possibility of losing salvation. Arminian theology views salvation as the result of cooperation between God's grace and human response, where grace is universally given but can be resisted by human free will. It also emphasizes that salvation is not a static status, but rather a dynamic relationship that requires perseverance in faith. This research shows that Arminianism not only provides a systematic soteriological framework, but is also relevant in the context of contemporary Christian faith life. By emphasizing God's inclusive love and human responsibility in responding to salvation, Arminianism provides an important contribution to contemporary theological discourse as well as a balanced faith appreciation between divine sovereignty and human freedom.